Biology of common carp in natural and farmed habitats from a global perspective - Rahman, Mohammad Mustafizur; Balcombe, Stephen Richard (NOVA Science Publishers, 2018)
Common carp (Cyprinus carpio L.) is an important food fish in many Asian and European countries, where it is considered as an important aquaculture species. Common carp account for approximately 4.1% of the total global aquaculture production and 9% of the global freshwater aquaculture production. The bulk of world’s common carp production (97%) comes from aquaculture. It is the most cultured fish species in Central and Eastern Europe, with production levels reaching more than 80% of total fish production in some countries. Aquaculture of this species is not observed in North America, New Zealand and Australia, where it is considered as a potential invasive and noxious aquatic species. Common carp belongs to the largest family (Cyprinidae) of freshwater fishes in the world. Their high adaptive capacity in a wide range of conditions and habitats accounts for their widespread distribution in most countries of the world. Presently, two subspecies exist in the world: the Asian (C. carpio haematopterus) and the European subspecies (C. carpio carpio). Common carp live in lakes, ponds, reservoirs, natural depressions and rivers. They are bottom dwellers, generally prefering to live near the soft vegetated sediments. They prefer benthic organisms particularly chironomids, oligochaetes, gastropods and other larval insects available in and on the benthos of natural habitats. When preferred foods become depleted, they shift their food habits, feeding niche and behaviour. The behaviour of common carp is consistent with classical optimal foraging theory. They redily adapt when inter and intra–specific competition are pronounced. Common carp significantly influence the behavior of other species (e.g. Labeo rorita) without showing any aggressive interactions. This article reviews the origin, habitats, distribution, growth, production, food habit, spawning, maturation, fecundity and behaviour of common carp focusing through a global lens.